An amelanotic melanoma of the rectum: report of a rare aggressive primary tumor - Singh, Swati; Singh, Sanjeev Kumar; Aggarwal, Roopak; Agarwal , Savita (International Journal of Research in Medical Sciences, 2023)
Anorectal melanoma is a rare and highly aggressive malignancy accounting for 0.4% to 1.6% of all melanoma and 0.5% of all anorectal cancer. About 80% cases are confused with haemorrhoids, rectal polyp, rectal ulcer or adenocarcinoma as they commonly present with rectal bleed. We herein reported a case of a 55-year male presenting with a 6-months history of vague abdominal pain, constipation, tenesmus, weight loss, and passage of blood in stool. Clinical examination and proctoscopy revealed a fungating mass. CT scan showed a mass involving lower rectum with periserosal infiltration. The patient underwent total abdominoperineal resection and specimen was sent for histopathological examination. Gross examination showed a fungating growth measuring 3.5×2.5×2 cm along with 8 lymph nodes. On microscopy rectal mucosa was normal, submucosa showed spindle shape tumor cells arranged in sheets & fascicles having pleomorphic nuclei, high N:C ratio with moderate amount of eosinophilic cytoplasm along with areas of necrosis and no evidence of lymphovascular emboli. 6/8 lymph nodes showed metastatic deposits along with large number of atypical mitotic figures. H and E examination suggested diagnosis of gastrointestinal stromal tumor (T2N1Mx). A panel of IHC markers was advised for definite diagnosis. The tumor cells were reactive for HMB45, S-100, Ki67 thus rendering a diagnosis of amelanotic melanoma. Due to absence/small numbers of melanin granules in H and E and diversity in morphology of neoplastic cells, misdiagnosis as lymphoma, gastrointestinal stromal tumor and sarcoma is very common. Hence IHC plays an indispensable role in the diagnosis of amelanotic melanoma of rectum.